OCD: DIAGNOSTIC APPROACH AND ASSESSMENT TOOLS - da Silva, Edvania da Paz; de Macedo, Ryan Rafael Barros; Baltazar Júnior, Orlando; Louzada, Rafael Cardoso; Bolzan, Amanda Camilla Schmidt; Freire, Vilma de Souza; Silva, Vitor de Castro; Gomes, Bruno da Silva; Marchesan, Luis Alexandre Lago; Matias, Maryah Edwarda Natan Rodrigues; Ribeiro, Michell Magalhaes (Seven Editora, 2026)
Obsessive-Compulsive Disorder (OCD) is a chronic and potentially disabling psychiatric condition characterized by the presence of obsessions, compulsions, or both, that cause significant distress and functional impairment. Conceptual and diagnostic advances have resulted in relevant changes in the classification of the disorder, especially with the publication of the International Classification of Diseases – 11th edition (ICD-11) by the World Health Organization (WHO). This defines it as: “persistent obsessions and/or compulsions that are recognized as excessive and cause significant distress or functional impairment.” This article aims to review the main diagnostic approaches to OCD, as well as the assessment tools most used in clinical practice, with emphasis on the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS). This article discusses the clinical implications of the new diagnostic classification of OCD, the differential diagnosis with other comorbid psychiatric conditions, the fundamentals, benefits, and main implications of first-line therapies—Exposure and Response Prevention (ERP) and Selective Serotonin Reuptake Inhibitors (SSRIs)—as well as the neurobiological evidence associated with the disorder. DOI: https://doi.org/10.56238/sevened2026.002-007